Relationship analysis and genetic diversity of tea Camellia sinensis germplasm from illegitimate seeds based on morphological characters - YUDITHIA MAXISELLY; CITRA BAKTI; MURGAYANTI MURGAYANTI; ERNAH ERNAH; ABDILLAH AZZAM WAHYUDIN; MUHAMAD KHAIS PRAYOGA; AGUNG KARUNIAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Maxiselly Y, Bakti C, Murgayanti, Ernah, Wahyudin AA, Prayoga MK, Karuniawan A. 2024. Relationship analysis and genetic diversity of tea Camellia sinensis germplasm from illegitimate seeds based on morphological characters. Biodiversitas 25: 3486-3495. Tea (Camellia sinensis (L.) O. Kuntze) is a plant with self-incompatible traits and requires significant efforts to assemble superior clones. The generation of the superior clone is from seed-derived genetic material that demands comprehensive information on population variance, genetic diversity, and the level of relationship among accessions. Therefore, this research aimed to determine population variances, genetic diversity, and relationships of tea germplasm accessions based on morphological characteristics. The experiment was conducted from August 2023 to January 2024 at the Indonesian Research Institute Tea and Cinchona, Mekarsari Village, Pasir Jambu District, Bandung Regency, West Java, Indonesia. An experimental method,